What endocardial right ventricular pacing site shows better contractility and synchrony in children and adolescents?. Issue 9 (26th August 2017) - Silvetti, Massimo Stefano; Ammirati, Antonio; Palmieri, Rosalinda; Pazzano, Vincenzo; Placidi, Silvia; Ravà, Lucilla; Remoli, Romolo; Saputo, Fabio Anselmo; Verticelli, Letizia; Drago, Fabrizio
Abstract: Aims: Right ventricular (RV) apical (RVA) pacing can induce left ventricular (LV) dyssynchrony, remodeling, and dysfunction in children with complete atrioventricular block (CAVB). We compared the functional outcome of RVA with RV alternative pacing sites (RVAPS), including para‐Hisian, septal, and outflow tract sites. Methods: This is a single‐center, retrospective study. Data were collected before pacemaker implantation (transvenous leads), postoperatively, at 6 months, and at 1–2–3–4 years. Electrocardiogram evaluation included QRS duration, axis, QTc/JTc, and QTc dispersion. Echocardiographic evaluation included 2‐D/3‐D assessment of ventricular dimensions (Z‐score of LV end‐diastolic dimension), function (ejection fraction), and synchrony. Results: From 2009 to 2015, 55 patients with CAVB, aged 3–17 years, with or without other congenital heart defects, underwent RVAPS (30 patients, median age 11 years) or RVA (25 patients, median 12 years). All leads were positioned into the septum. Before implantation, no significant differences in parameters were observed, except for higher Z‐score in RVAPS than in RVA. After implantation, at a median follow‐up of 2.5 (range 1–6) years, the two groups showed no significant differences in LV dimensions, contractility, and synchrony. QRS intervals of RVAPS were significantly shorter than RVA. Clinical status was good and contractility/synchrony indexes were normal or adequate in all patients. Conclusions: In pediatric patients, RVAPS and RVA showed no significant differences in LV dimensions, contractility, and synchrony. Preimplantation dilated patients showed LV reverse remodeling. RVAPS demonstrated shorter QRS intervals. Therefore, septal pacing sites, either RVA or RVAPS, seem to determine good contractility and synchrony at a mid‐term follow‐up.